Plasmid‐Based Donor Templates for Nonviral CRISPR/Cas9‐Mediated Gene Knock‐In in Human T Cells. Issue 9 (21st September 2022) - Senger, Kate; Akhmetzyanova, Ilseyar; Haley, Benjamin; Rutz, Sascha; Oh, Soyoung A.
Abstract: Effective and precise gene editing of T lymphocytes is critical for advancing the understanding of T cell biology and the development of next‐generation cellular therapies. Although methods for effective CRISPR/Cas9‐mediated gene knock‐out in primary human T cells have been developed, complementary techniques for nonviral gene knock‐in can be cumbersome and inefficient. Here, we report a simple and efficient method for nonviral CRISPR/Cas9‐based gene knock‐in utilizing plasmid‐based donor DNA templates. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Purification of human CD4 + or CD8 + T cells from blood Basic Protocol 2 : Activation of purified CD4 + or CD8 + T cells using TransAct CD3/CD28 agonist‐conjugated nanomatrix Basic Protocol 3 : Preparation of Cas9/sgRNA RNPs Basic Protocol 4 : Transfection of CAS9‐RNP and knock‐in template into human T cells Support Protocol 1 : Purity check following magnetic T cell isolation Support Protocol 2 : Dextramer staining of TCR‐edited T cells Support Protocol 3 : Functional characterization of TCR knock‐in T cells Support Protocol 4 : Detection of knock‐in reporter activity in CRISPR/CAS9‐edited T cells